2014
DOI: 10.1080/07373937.2014.949347
|View full text |Cite
|
Sign up to set email alerts
|

Application of Intermediate-Wave Infrared Drying in Preparation of Mushroom Chewing Tablets

Abstract: Two drying methods, namely intermediate-wave infrared drying (IWIR) and hot-air drying (HA), were compared in preparation of mushroom chewing tablets (MCT). It was observed that IWIR enhanced the drying rate and shortened the time required for MCT. IWIR technology was better than HA in preserving thermalsensitive materials by thermo gravimetric analysis. In addition, IWIR had a significant effect on the flavor of the samples, which would be used for retaining flavor ingredients and be conducive to the processi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(10 citation statements)
references
References 28 publications
2
8
0
Order By: Relevance
“…The outcome from this work revealed a positive impact in respect of TPC and TFC of the ginger (i.e., enhanced TPC and TFC). Our findings are in agreement with the previous study of Wang, Zhang, Fang, and Xu () and An et al (), who reported that IR‐dried mushroom and ginger retained a greater percentage of the TPC and TFC.…”
Section: Resultssupporting
confidence: 94%
“…The outcome from this work revealed a positive impact in respect of TPC and TFC of the ginger (i.e., enhanced TPC and TFC). Our findings are in agreement with the previous study of Wang, Zhang, Fang, and Xu () and An et al (), who reported that IR‐dried mushroom and ginger retained a greater percentage of the TPC and TFC.…”
Section: Resultssupporting
confidence: 94%
“…The results of this research showed a positive effect on the TFC of dried ginger (i.e., improved TFC). Our findings are consistent with those ofWang et al (2014), who found that IR-dried mushrooms retained a higher percentage of TFC.It is worth noting that the FD samples conserved a greater quantity of the TFC than the PVD, MC-and IR-dried samples. This may be ascribed to the slow drying rate and minimal heat during the drying process which enhanced the preservation of the flavonoids.…”
supporting
confidence: 92%
“…The reason for this result is that the infrared radiation transfers thermal energy in the form of electromagnetic waves, an innovative characteristic of infrared drying (Krishnamurthy, Khurana, Jun, Irudayaraj, & Demirci, ). Wang, Zhang, Fang, and Xu () noted that infrared drying accelerated the drying process and assisted in preserving thermal‐sensitive materials in the dried products. Our results are in line with the results of Sui, Yang, Ye, Li, and Wang () who reported that the highest proanthocyanidin content was retained in wine grape pomace during infrared drying as compared to conventional drying.…”
Section: Resultsmentioning
confidence: 99%